Laying Performance of Wareng Chicken under Free Choice Feeding and Different Cage Density - S Iskandar (Faculty of Animal Science, Bogor Agricultural University, 2011)
The aim of the experiment was to explore the possibility of using free choice feeding technique under different cage density for unselected native chicken. Eighty hens of laying Wareng chicken were divided into two feeding systems. Half of them were fed complete commercial diet of 17% crude protein, with 2800 kcal ME/kg and the other half were subjected to free choice diet. The diets were in mash form and placed in sufficient feed troughs in front of each cage. Each cage was occupied by four or six hens. Free choice feeding hens were served with commercial concentrate (30% crude protein), ground corn and oyster shell, placed separately in feed troughs. Observation was carried out during 24 weeks laying period, starting from 20 to 44 weeks of age. The results showed that egg production (9.35% hen day), and the intake of feed (42.74 g/day), protein (7.01 g/day), energy (116.6 kcal ME/day), calcium (1.99 g/day and phosphorus (0.22 g/day) were not affected (P>0.05) by feeding system nor by cage density. The results however indicated that free choice feeding technique provided sufficient nutrients in supporting maximum egg production of unselected native chicken.